The Influence of Remuneration, Work Environment, and Workload on Organizational Commitment and Employee Performance at Pondok Pesantren Islam Ulul Albab - Imam Muttaqin, Ahsan; Juwaini, Ahmad; Hartono, Rudi (LPPM Universitas Jambi, 2026)
This study examines the influence of remuneration, work environment, and workload on organizational commitment and employee performance at Pondok Pesantren Islam (PPI) Ulul Albab, South Lampung, Indonesia. An explanatory quantitative approach with a cross-sectional design was employed. Data were collected using a four-point Likert-scale questionnaire from 69 permanent employees (a 71.8% response rate out of a population of 96, obtained through total sampling) and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1.1.8. Hypothesis testing shows that work environment has a positive and highly significant effect on both organizational commitment and employee performance. Remuneration significantly strengthens organizational commitment but has no significant effect on performance. Workload shows no significant effect on organizational commitment, yet has a positive and significant effect on employee performance, contrary to the initially hypothesized direction. The model explains 73.2% of variance in organizational commitment (strong) and 32.6% in employee performance (moderate). Within a religiously grounded pesantren work ecosystem, a socially and spiritually conducive work environment is the primary driver of commitment and productivity. Remuneration reinforces emotional attachment, while workload, reframed as religious trust, functions as a productive challenge. These findings offer strategic implications for designing holistic human resource policies aligned with Islamic values.